2022
DOI: 10.3389/fmicb.2022.979388
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and mechanism of malondialdehyde against Staphylococcus xylosus and Lactiplantibacillus plantarum isolated from a traditional Chinese dry-cured fish

Abstract: Malondialdehyde (MDA) is one of the most representative reactive carbonyl species (RCSs) produced by lipid oxidation in food. However, the inhibitory effect of MDA on microorganisms has received little attention. Thus, the aim of this study was to reveal the antibacterial mechanism of MDA on Staphylococcus xylosus and Lactiplantibacillus plantarum isolated from dry-cured fish. The results showed that the minimum inhibitory concentrations (MICs) of MDA on S. xylosus and L. plantarum were 90 μg/ml and 180 μg/ml,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…This shows that the stress resistance of C. pilosula is low in the summer and enhanced in the autumn [70][71][72]. Zhang et al [73] showed that MDA has antibacterial properties against bacteria such as Staphylococcus and Lactobacillus. Bacteria, such as Exiguobacterium and Nitrospira, play an important role in improving stress resistance and biodegradation in plants [74][75][76].…”
Section: Discussionmentioning
confidence: 94%
“…This shows that the stress resistance of C. pilosula is low in the summer and enhanced in the autumn [70][71][72]. Zhang et al [73] showed that MDA has antibacterial properties against bacteria such as Staphylococcus and Lactobacillus. Bacteria, such as Exiguobacterium and Nitrospira, play an important role in improving stress resistance and biodegradation in plants [74][75][76].…”
Section: Discussionmentioning
confidence: 94%
“…The release of intracellular nutrients might be the primary mechanism of microbial inactivation. On the other hand, unsaturated lipid acids on the cell membrane could be rapidly oxidized to peroxides such as MDA when damaged due to the presence of CC. , MDA accumulation led to oxidative stress and cross-linking reactions, exacerbating cell membrane damage . As demonstrated in Figure B, MDA accumulation in response to UnCA activation indicated the lipid peroxidation of the cell membrane and would continue to oxidize the lipid and protein on the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 MDA accumulation led to oxidative stress and cross-linking reactions, exacerbating cell membrane damage. 28 As demonstrated in Figure 2B, MDA accumulation in response to UnCA activation indicated the lipid peroxidation of the cell membrane and would continue to oxidize the lipid and protein on the cell membrane. Therefore, the hydrophobicity of MCCA was believed to contribute to damage of cell membranes, causing cell membrane leakage and oxidative stress.…”
Section: Recovery Of Methanogenesis Aftermentioning
confidence: 93%
“…Malondialdehyde (MDA), one of the most representative reactive carbonyl species (RCSs) produced by lipid oxidation in bacteria [19] and in food [14], has received extensive attention recently. However, the inhibitory effect of MDA on microorganisms has received little attention.…”
Section: Anti-biofilm Effect Of Malondialdehyde (Mda) Via Cell Membra...mentioning
confidence: 99%
“…Moreover, FT-IR studies showed that MDA might affect the molecular composition of S. xylosus and L. plantarum cells. These changes indicated the negative influence of MDA on cell membrane and cellular homeostasis [14].…”
Section: Anti-biofilm Effect Of Malondialdehyde (Mda) Via Cell Membra...mentioning
confidence: 99%